Peningkatan Hasil Belajar Siswa Melalui Metode Inkuiri pada Materi Perlakuan Khusus di Kelas XI ATPH SMKN 1 Gondang - Fifi Rosyidah; Marmi Marmi; Achmadi Achmadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research aims to improve student learning outcomes through the inquiry method on the subject of special treatment of fruit plant seeds. The study was conducted as classroom action research (CAR) at SMKN 1 Gondang for class XI Agribusiness of Food Crops and Horticulture (ATPH). The research was carried out in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through tests and observation sheets. The results show that the inquiry method significantly improves student engagement and cognitive outcomes. Average class performance increased from 62% in Cycle I to 85% in Cycle II. These findings suggest that inquiry-based learning can enhance students' critical thinking and understanding in agricultural subjects.